Navigating Inflation : Analyzing the Influence of Inflation on Business Valuation and Valuation Metrics - Seman, Juraj; Krabec, Tomáš, 1981-; Šmídová, Radana, 1977-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
This master thesis examines the impact of inflation on business valuation and valuation metrics by assessing the influence of inflation through valuation models based on discounted cash flow (DCF) method. The research involves modelling DCF models under various inflation rates and expectations to simulate different inflationary scenarios, providing insights into the behaviour of business value and valuation metrics. The findings of this research should contribute to the understanding of how inflation affects business valuation and relevant valuation metrics.
Vedoucí práce: Tomáš Krabec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses